Functional characteristics of restaurant business management in an innovative economy - Kolisnychenko Tatiana; Колісниченко Тетяна (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. Innovation is one of the important sources of competitive advantage for the restaurant business in the era of the latest technologies and means of communication. In the innovative economy, the sphere of the restaurant business is transformed into a completely new one, changing its own technological, process, operational basis. The purpose of the article is to generalize the functional characteristics of restaurant business management in the conditions of the innovative economy, to identify their specific effects on the development of the restaurant business. The following research methods were used in the article: the method of analysis, generalization and synthesis, a systematic approach to systematize the functional characteristics of restaurant business management. It has been established that the innovative economy is characterized by qualitative changes, which should include technical and technical progress, the introduction of innovation, etc. Under such conditions, the effective and efficient management of the restaurant business should take place thanks to the implementation of functional characteristics. The latter combine the purpose of the restaurant business, principles and standards of its management process, restaurant business development objectives, restaurant business guidelines, functions and tools of the restaurant business management system, influencing factors and laws of economic influence on the development, the means of the restaurant business operation business. The main task to combine all characteristics and use them in the course of restaurant business management. Elaboration of these important problems requires further empirical research, which will provide a basis for diagnosing the current situation and preparing an innovative strategy for the development of the restaurant business, taking into account the peculiarities of the functioning of the innovative economy.

A legújabb technológiák és kommunikációs eszközök korszakában az innováció az éttermi üzletág versenyelőnyének egyik legfontosabb forrásává vált. Az innovatív gazdaságban az éttermi üzletág teljesen új területté alakul át, megváltoztatva saját technológiai, folyamati és működési alapjait. A cikk célja, hogy általánosítsa az éttermi üzletvezetés funkcionális jellemzőit az innovatív gazdaságban, azonosítsa azok konkrét hatásait az éttermi üzletág fejlődésére. A cikkben a következő kutatási módszereket alkalmaztuk: az elemzés, az általánosítás és a szintézis módszerét, szisztematikus megközelítést az éttermi üzletvezetés funkcionális jellemzőinek rendszerezésére. Megállapítást nyert, hogy az innovatív gazdaságot minőségi változások jellemzik, amelyeknek magukban kell foglalniuk a műszaki és technológiai fejlődést, az innováció bevezetését stb. Ilyen feltételek mellett az éttermi üzletág hatékony és eredményes irányítása olyan funkcionális jellemzők megvalósításának segítségével valósulhat meg, amelyek ötvözik az éttermi üzletág célját, az éttermi üzletvezetési folyamat alapelveit és standardjait, az éttermi üzletág fejlesztésének feladatait, irányelveit, rendszer funkcióit és eszközeit, továbbá az éttermi üzletág fejlődésére gyakorolt gazdasági befolyásolás törvényeit, fejlődésének feltételeit, működésének eszközeit, valamint az éttermi üzletág fejlődését befolyásoló tényezőket. A legfőbb feladat – az összes jellemző egységesítésének mértékének és felhasználásának ismerete az éttermi üzletvezetés során. Ezen fontos problémák feltárása további empirikus kutatást igényel, amely alapot ad a jelenlegi helyzet diagnosztizálásához és az innovatív gazdaság működésének sajátosságait figyelembe vevő innovatív stratégia elkészítéséhez az éttermi üzletág fejlesztése érdekében.

Резюме. Інновації є одним із важливих джерел формування конкурентної переваги для сфери ресторанного бізнесу в епоху новітніх технологій та засобів комунікації. В інноваційній економіці сфера ресторанного бізнесу трансформується на абсолютно нову, змінюючи власну технологічну, процесну, операційну основу. Метою статті є узагальнення функціональних характеристик управління ресторанним бізнесом в умовах інноваційної економіки, виявлення їх особливостей впливу на розвиток ресторанного бізнесу. У статті було застосовано такі методи дослідження: метод аналізу, узагальнення та синтезу, системний підхід для систематизації функціональних характеристик управління ресторанним бізнесом. Встановлено, що інноваційній економіці притаманні якісні зміни, до яких варто віднести техніко-технічний прогрес, впровадження інновації тощо. За таких умова результативне й ефективне управління ресторанним бізнесом має відбуватись завдяки забезпеченню впровадження функціональних характеристик, які поєднують мету діяльності ресторанного бізнесу, принципи і стандарти процесу управління ресторанним бізнесом, задачі розвитку ресторанного бізнесу, орієнтири діяльності ресторанного бізнесу, функції й інструменти системи управління ресторанним бізнесом, закони економічного впливу на розвиток ресторанного бізнесу, умови розвитку ресторанного бізнесу, засоби функціонування ресторанного бізнесу, чинники впливу на розвиток ресторанного бізнесу. Основним завданням є ступінь об’єднання усіх характеристик та їхнє використання у ході управління ресторанним бізнесом. Опрацювання цих важливих проблем потребує проведення подальших емпіричних досліджень, які забезпечать основу для діагностики поточної ситуації та підготовки інноваційної стратегії розвитку ресторанного бізнесу з урахуванням особливостей функціонування інноваційної економіки.
Az éttermi üzletvezetés funkcionális jellemzői az innovatív gazdaságban
Функціональні характеристики управління ресторанним бізнесом в інноваційній економіці
https://aab-economics.kmf.uz.ua/aabe
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010508
Keywords: innovations; restaurant business; management; functional characteristics; innovative economy